2002
DOI: 10.1111/j.1530-0277.2002.tb02460.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure and Attachment Behavior in Children

Abstract: Although prenatal alcohol exposure was found to relate to higher levels of insecure attachment, children of mothers who provided them with emotional support were more able to deal with frustration. These children also exhibited higher levels of attachment security. Thus, the mother's supportive presence may mediate the association between prenatal alcohol exposure and the child's security of attachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 78 publications
7
36
1
2
Order By: Relevance
“…These alcohol-exposed children were living in poverty with their biological mothers, the majority of whom were single parents. With this group of primarily Black non Hispanic motherchild dyads, divided into two PAE groups (abstinent light or moderateheavy), we again found a significant association between alcohol exposure during pregnancy and attachment security [O'Connor et al, 2002a]. Strikingly, 80% of children in the moderateheavy alcohol exposed group displayed attachment behaviors classified as insecure, while only 36% of children in the abstinent-light group showed insecure attachments.…”
Section: Infancy and Early Childhoodmentioning
confidence: 58%
See 1 more Smart Citation
“…These alcohol-exposed children were living in poverty with their biological mothers, the majority of whom were single parents. With this group of primarily Black non Hispanic motherchild dyads, divided into two PAE groups (abstinent light or moderateheavy), we again found a significant association between alcohol exposure during pregnancy and attachment security [O'Connor et al, 2002a]. Strikingly, 80% of children in the moderateheavy alcohol exposed group displayed attachment behaviors classified as insecure, while only 36% of children in the abstinent-light group showed insecure attachments.…”
Section: Infancy and Early Childhoodmentioning
confidence: 58%
“…These temperamental differences in early infancy may set the stage for maladaptive mother-infant interactions and subsequent socioemotional problems as the child matures. Several of our studies have incorporated this diathesis stress model to explain the relation between PAE and internalizing symptoms in infancy and early childhood [O'Connor et al, 1992;O'Connor and Kasari, 2000;Carmichael Olson et al, 2001;O'Connor, 2001;O'Connor et al, 2002a;O'Connor and Paley, 2006]. For example, in an early study, we examined a low-risk sample of 1-year-old children born to predominantly White non Hispanic, well-educated, middle class, married birth mothers who considered themselves social drinkers [O'Connor et al, 1992].…”
Section: Infancy and Early Childhoodmentioning
confidence: 99%
“…In a separate higher-risk sample, O'Connor et al found that when children have higher levels of cumulative risk in the larger social context, such as poverty or living with a single parent, this negative developmental trajectory worsens [O'Connor et al, 2002]. Of interest, 80% of children exposed prenatally to alcohol showed insecure attachment (a pivotal developmental feature) while, even in this high-risk sample, only 36% of the nonexposed children displayed attachments rated as insecure.…”
Section: A Developmental Systems Studymentioning
confidence: 99%
“…O'Connor, Sigman, and Kasari (1992) surveyed children of socially drinking mothers and found prenatal alcohol exposure to be related to negative affect at 1 year. Negative affect mediated the influence of prenatal alcohol exposure on the mother-infant interaction (O'Connor, Sigman, & Kasari, 1993), indicating that prenatal alcohol exposure can predispose children to be more irritable, which in turn may have a negative impact on the mother-infant relationship (O'Connor, Kogan, & Findlay, 2002). Among girls, prenatal alcohol exposure and negative affect at 1 year were associated with depressive symptoms at the age of 6 years (O'Connor, 2001).…”
Section: Prenatal Alcohol Exposurementioning
confidence: 99%